Newros Bairam in Turkish World - Aras, Enver (Giresun Üniversitesi, 2021)
Newros is a religious festival formed with the national, sacred, philosophical, social, and aesthetical thought of the Turks and having important tasks in the formation of the national culture. Newros we face within many of our legends and epics is one of the oldest Turkish bairams putting forth the relationships of the human, nature, and God with respect to the religion ‘Sky God’. As it is known, natural conditions change according to the seasons. Humans also try to adapt the changing natural conditions. Newros means the beginning of a new year implying the revival of nature. Newros, achieving some mythological, legendary, and religious features among Turks before Islam and including some religious applications after Islam, has been celebrated as a national bairam for ages.

Nevruz, Türklerin millî, manevî, felsefî, sosyal, estetik düşünceleriyle şekillenen ve millî kültürün oluşmasında önemli görevler üstlenen bir bayramdır. Birçok destan ve efsanemizde de karşımıza çıkan Nevruz, ‘Gök Tanrı’ dini çerçevesinde insan, tabiat ve Tanrı münasebetlerini öne çıkaran en eski Türk bayramlarından biridir. Bilindiği üzere tabiat şartları mevsimlere göre değişiklik gösterir. İnsanlar da değişen tabiat şartlarına uyum sağlamaya çalışır. İşte Nevruz, tabiatın yeniden dirilişini ifade eden yeni bir yılın başlangıcı demektir. İslâmiyet’ten önce Türk boyları arasında birtakım mitolojik, efsanevî ve dinî özellikler kazandırılan, İslâmiyet’ten sonra da bazı dinî uygulamalar dahil edilen Nevruz, eskiden beri millî bir bayram olarak kutlana gelmiştir.
TÜRKLERDE NEVRUZ BAYRAMI
Keywords: Political Science; Siyaset Bilimi